Purple Sweet Potato Fortified Feeding as an Effective Intervention to Improve Toddler Undernutrition - Lestari Lestari; Wahyu Ningsih Lase; Evi Martalinda Harefa; Lismawati Pertiwi Waruwu; Viktor Trismajaya Hulu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Malnutrition is a condition in which an individual has nutrient intake below adequate levels, leading to impaired growth and development. Efforts to prevent malnutrition in toddlers can be implemented through supplementary feeding based on local food ingredients, including purple sweet potato. This study aimed to determine the effect of purple sweet potato–based supplementary feeding on the nutritional status of underweight toddlers in the Gunungsitoli City area. A quasi-experimental design with pretest–posttest and a control group was employed. The study population consisted of all malnourished toddlers, and a total sample of 20 children was selected using purposive sampling, comprising 10 in the intervention group and 10 in the control group. Before receiving purple sweet potato–based supplementary feeding, most toddlers in the intervention group were categorized as underweight (70%) and of normal height (70%), whereas in the control group, the majority were underweight (60%) and stunted (50%). After the intervention, most toddlers in the intervention group achieved normal weight (90%) and normal height (70%), with a significance value of 0.002 (p<0.05). In contrast, the control group remained predominantly underweight (80%) and stunted (50%), with a significance value of 0.08 (p>0.05). These findings indicate that purple sweet potato–based supplementary feeding positively affects the nutritional status of underweight toddlers, as reflected in improvements in both weight and height.Keywords: purple sweet potato; supplementary feeding; toddler undernutrition status